Pemanfaatan Lahan Pertanian Desa Teuladan, Aceh Besar untuk Budidaya Nilam Berkelanjutan - Hazful Maizi; Friesca Erwan; Yulia Sawitri; Aisyah Juliawulan Malahayati; Zaudhatul Ulya; Meutia Fadilla; Awal Aflizal Zubir; Hifnalisa Hifnalisa; Muhibbuddin Muhibbuddin; Geta Ambartiasari (Universitas Muhammadiyah Semarang, 2025)
The global demand for patchouli oil as a raw material in the perfume industry is considerably high. However, the supply from exporting countries, particularly Indonesia, remains suboptimal. Aceh Province, one of Indonesia's key producers of patchouli oil, has been expanding its patchouli farming areas as a strategy to enhance productivity. Nevertheless, not all agricultural lands are suitable for patchouli cultivation. Therefore, it is essential to identify agricultural land resources that are ideal and sustainable for patchouli farming. The utilization of new potential lands could positively impact patchouli oil productivity. Land identification and mapping were carried out through observations and by utilizing candidate land indicator instruments. These indicators include land quality, land type, accessibility, land security systems, drainage systems, water sources, groundwater quality, and vulnerability to natural disasters. This article outlines the stages of community engagement activities conducted to identify the potential for patchouli farming in Teuladan Village, Lembah Seulawah Subdistrict, Aceh Besar Regency. The process involved program socialization, focus group discussions (FGDs), and interviews with farmers using candidate land surveys. The findings indicate that the agricultural land in Teuladan Village is suitable for sustainable patchouli cultivation. With the availability of ideal land and sufficient knowledge of proper patchouli cultivation practices, it is anticipated that high-quality patchouli oil can be produced. This will directly contribute to improving the welfare of the local community, particularly the farmers in Teuladan Village.